Nano sodalite as solid base catalyst for knoevenagel condensation reaction - Teow, Bee Khuan (2010)
Sodalite is a type of zeolite with ultramicroporesize and has high thermal stability. Sodalite with nanosized particle with increased in external surface area offers great attractive possibilities to explore their potential utilization. In this study, nanosized sodalite with low Si/Al ratio was synthesized and used as base catalyst in Knoevenagel condensation reaction. The synthesis was performed using fumed silica in the alkali medium with molar ratio of 19Na2O:4SiO2:1Al2O3:190H2O at various temperature and time of crystallization. The samples were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and Field emission scanning electron microscopy (FESEM). Results showed that, pure nanosodalite crystals with average crystal size of 40 to 80 nm have been successfully been synthesized during 5 hours of heating at 60 °C under static condition. Pure microsized sodalite was obtained when the synthesis temperature was increased to 90 °C. Basicity measurement using CO2 as probe molecule and monitored by FTIR revealed the presence of basic site with the appearance of vibration band at 1430 cm- 1. The catalytic activities of the nano and micro-sodalite were evaluated for base catalyzed reactions via Knoevenagel condensation between benzaldehyde and malononitrile producing benzylidenemalononitrile as the only product. The results showed that both nano- and micro-sodalite catalysts were active for the reaction where the conversion of benzaldehyde for the nanosodalite(S8) and microsodalite (S15) was 92.% and 88.7%, respectively. Based on the GC analysis, all the catalyst are found to give 100 % of product selectivity to the main product benzylidenemalononitrile.